Adolescent pregnancy in Sao Tome and Principe - Vasconcelos, Alexandra (2022)
Funding Information: AV was supported by the Fundação para a Ciência e Tecnologia (FCT) ( https://www.fct.pt/index.phtml.pt/ ), grant number SFRH/BD/117037/2016. The funder had no role in study design, data collection and analysis, decision to publish or preparation of the manuscript. Publisher Copyright: © 2022, The Author(s).